From Youthful Vigor to Aging Decline: Unravelling the Intrinsic and Extrinsic Determinants of Hippocampal Neural Stem Cell Aging - Jiménez Peinado, Patricia; Urbach, Anja (Cells (Basel, Switzerland), 2023)
Since Joseph Altman published his pioneering work demonstrating neurogenesis in the hippocampus of adult rats, the number of publications in this field increased exponentially. Today, we know that the adult hippocampus harbors a pool of adult neural stem cells (NSCs) that are the source of life-long neurogenesis and plasticity. The functions of these NSCs are regulated by extrinsic cues arising from neighboring cells and the systemic environment. However, this tight regulation is subject to imbalance with age, resulting in a decline in adult NSCs and neurogenesis, which contributes to the progressive deterioration of hippocampus-related cognitive functions. Despite extensive investigation, the mechanisms underlying this age-related decline in neurogenesis are only incompletely understood, but appear to include an increase in NSC quiescence, changes in differentiation patterns, and NSC exhaustion. In this review, we summarize recent work that has improved our knowledge of hippocampal NSC aging, focusing on NSC-intrinsic mechanisms as well as cellular and molecular changes in the niche and systemic environment that might be involved in the age-related decline in NSC functions. Additionally, we identify future directions that may advance our understanding of NSC aging and the concomitant loss of hippocampal neurogenesis and plasticity.